Justicia perlisensis, a new name for Justicia rupestris Ridl. (Acanthaceae) - Soumya, Puliyakode; Goswami, Samrat; Sunojkumar, Purayidathkandy; Dash, Sudhansu Sekhar (Phytotaxa, 2025)
Justicia L., one of the largest and most diverse genera in the family Acanthaceae, comprises approximately 1000 species worldwide (Manzitto-Tripp et al. 2022). Taxonomic studies on Justicia in Asia have been conducted by several authors (Anderson 1867, Clarke 1885, Ridley 1911, Craib 1912, Imlay 1938, Hansen 1985, Cramer 1998, Wood 2001, Hu et al. 2011, Bhattacharya & Karthigeyan 2023). However, a detailed study of this genus in the Malay Peninsula was first conducted by Clarke (1908) with a report of 18 species and later by Ridley (1923), who documented 30 species in the Flora of the Malay Peninsula.